The Importance of Ion Channels in Maintaining Cell Membrane Stability - Yoqubova Nargiza Abdurasul kizi; Chuliyev Ikrom Ne’matullayevich (Periodica Journal, 2022)
The basis of vital processes in biological organisms is the processes that take place directly at the cellular level. As a result of complex processes taking place in the cell membrane, many important vital processes take place, such as excitation, photosynthesis, and respiration. The cell membrane is generally composed of a lipid layer containing protein molecules. Protein molecules in the lipid layer on the membrane mainly form ion channels, ion pumps and receptors. The protein molecules that make up the ion channel in the membrane have the ability to selectively select a specific ion along a chemical gradient. Ion channels are divided into groups depending on the mechanisms of opening and closing, depending on the potential, sensitive to the action of ligands or activated by mechanical action
Keywords: cell; membrane; living organisms; ion channels